French Politics and Society - Cole, Alistair (Pearson Longman, 2005)
Assuming no previous knowledge and concentrating on the post-1981 era, this book introduces the fundamentals of French government and society. Covering a broad spectrum of topics, French Politics and Society 2nd Edition follows a logical structure and framework for analysis, providing an excellent description of French institutions, access to background information and discussions of historical developments, political forces, public policy, and the evolution of important aspects of French society.